Artifact dualism, materiality, and the hard problem of ontology: Some critical remarks on the Dual Nature of Technical Artifacts Program - Vaccari, Andrés Pablo (2013)
Fil: Vaccari, Andrés P. Universidad Nacional de Río Negro. Centro Interdisciplinario de Estudios Sobre Territorios, Economía y Sociedad. Río Negro; Argentina